The Effect of E-Commerce on Purchase Decision at Wingko Babat NN. Meniko - Michael Hans (Journal of Management and Business Environment (JMBE), 2024)
The study aims to determine the effect of e-commerce on purchase decision in the case of the online store of Wingko Babat NN. Meniko at Tokopedia. It applies a quantitative approach with four independent variables comprising ease of use, trust, information quality, and service quality and dependent variable of purchase decision. The data was collected using questionnaire which had been tested for its validity and reliability prior to its distribution and was analyzed using multiple linear regression analysis. The results show that partially ease of use, trust, information quality, and service quality do not significantly influence purchase decision. However, they simultaneously have a significant effect on purchase decision.